Student preferences over module design - Joshua Fullard (Springer, 2024)
Abstract In this paper we use new experimental data to investigate students' preferences regarding lecture mode and length, and assessment type across two unique dimensions: expected learning and enjoyment. Our main findings are as follows: first, students demonstrate a strong preference against online lectures. Students expect to learn more from, and enjoy, modules that have in-person lectures. Given that one-third of lectures in UK universities are now taught online-up from 4 percent before the pandemic-these results indicate a misalignment with students' preferences. Second, students favour shorter lectures (1 h) over longer lectures (2 h). Students do not expect to learn more from longer lectures-suggesting diminishing expected marginal returns. Third, students prefer individual assignments to exams. Students expect to enjoy and learn more from modules that have individual assignments (as opposed to exams). These findings are robust across two samples of university students.